A Revised Structure and Assigned Absolute Configuration of Theissenolactone A - Melissa M. Cadelis; Soeren Geese; Lauren Gris; Bevan S. Weir; Brent R. Copp; Siouxsie Wiles (Molecules, 2020)
Antimicrobial bioassay-guided fractionation of Microcera larvarum led to the isolation of a γ-lactone with a furo[3,4-b]pyran-5-one bicyclic ring system (1) and three known compounds, (3S,4R)-4-hydroxymellein (2), (3S,4S)-4-hydroxymellein (3) and 7-hydroxy-3-(1-hydroxyethyl)isobenzofuran-1(3H)-one (4). Structure elucidation was conducted by NMR spectroscopic methods. Absolute configuration of 1 (2R, 3S, 5S, 7S, 8R) was established using the chiral derivatizing agent MPA and was fully supported by calculated specific rotation and ECD spectra. The spectroscopic data observed for 1 were identical to those previously reported for theissenolactone A (7), necessitating a correction of the latter (from C-5/C-8 trans ring fusion to cis). Compounds 1–4 were evaluated for antimicrobial activity against a panel of pathogens.